High Flow Nasal Cannula Decreased Pulmonary Complications in Neurologically Critically Ill Patients - Wang, Shuanglin; Yang, Jingjing; Xu, Yanli; Yin, Huayun; Yang, Bing; Zhao, Yingying; Wei, Zheng Zachory; Zhang, Peng (Frontiers in Human Neuroscience, 2022)
Objective: Pulmonary complications could badly affect the recovery of neurological function and neurological prognosis of neurological critically ill patients. This study evaluated the effect of high-flow nasal cannula (HFNC) therapy on decreasing pulmonary complications in neurologically critically ill patients. Patients and Methods: The patients admitted to the intensive care unit (ICU) with serious neurological disease and receiving oxygen therapy were retrospectively reviewed (Ethical No. IRB2021-YX-001). Patients were divided into the HFNC group and the conventional oxygen therapy (COT) group. We analyzed the data within these two groups, including patients’ baseline data, short-term outcomes of respiratory complications, general outcomes including hospital stay, ICU stay and mortality, and neurological functions. To analyze the relevant factors, we performed multivariable logistic regression analysis. Results: A total of 283 patients met the criteria, including 164 cases in the HFNC group and 119 cases in the COT group. The HFNC group had remarkably less mechanical ventilation requirement with lower phlegm viscosity. Even more, ICU stay and total hospital stay were significantly shortened in the HNFC group. Conclusion: HFNC decreased pulmonary complications in neurologically critically ill patients and improved recovery of neurological function and neurological prognosis.